Evaluation of Field Work Practices (FWP) in the Independent Curriculum: Multi-Site Study in Vocational Schools - Chrisnanto, Rafli; Haq, Mohammad Syahidul; Amalia, Kaniati; Khamidi, Amrozi; Nursalim, Mochammad (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the implementation of Field Work Practice (FWP) in the Independent Curriculum in two Vocational High Schools (SMK), namely SMKN 1 Driyorejo and SMKN 1 Duduksampeyan. As part of vocational education, street vendors play a strategic role in preparing vocational school graduates to have technical competence and work ethic according to the needs of the business and industry (BI). This study uses the CIPP (Context, Input, Process, Product) evaluation model with a descriptive qualitative approach. Data was collected through 18 in-depth interviews, 4 direct observations, and analysis of supporting documents, involving principals, vice principals, supervisors, students, parents, and industry partners. The results of the study show that in general, the implementation of street vendors has met the set standards and has a positive impact on students' work readiness. However, several aspects of input and processes were found that still needed to be improved, especially in the synchronization of the curriculum and the debriefing of participants before the implementation of street vendors. These findings indicate that the street vendor program in the Independent Curriculum has great potential to create adaptive, productive, and competent graduates, noting the importance of continuous improvement in planning and partnership with BI.